cardiology 2017
DOI: 10.35841/cardiology.1.2.55-59
|View full text |Cite
|
Sign up to set email alerts
|

It?s time to focus on decreasing cardiovascular mortality in NAFLD population: potential use of statins and PCSK9 inhibitors.

Abstract: With the alarming rise in prevalence of nonalcoholic fatty liver disease (NAFLD) in the world, there is an increasing need to recognize the strong association between NAFLD and cardiovascular disease (CVD). NAFLD is dynamically involved in the pathogenesis of CVD through the processes that include increased oxidative stress, endothelial dysfunction, accelerated progression of atherosclerosis, and irregular fatty acid, glucose, and lipoprotein metabolism. By reviewing and understanding the mechanisms, the aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…If utilized appropriately, it can be used to diagnose or guide the management of a variety of life-threatening conditions. 1 Drew et al 2 conducted a study to determine the electrocardiography utilization among emergency medical services (EMS) staff in managing patients with acute coronary syndrome (ACS); their results indicated that the increased use of pre-hospital electrocardiography reduced hospital treatment times. However, many studies concluded that there was underutilization of EMS systems by ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…If utilized appropriately, it can be used to diagnose or guide the management of a variety of life-threatening conditions. 1 Drew et al 2 conducted a study to determine the electrocardiography utilization among emergency medical services (EMS) staff in managing patients with acute coronary syndrome (ACS); their results indicated that the increased use of pre-hospital electrocardiography reduced hospital treatment times. However, many studies concluded that there was underutilization of EMS systems by ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…MAFLD is currently the most common liver disease, affecting more than 25% of the adult population worldwide, with incident rates expected to rise [14,15]. MAFLD is a risk factor for cardiovascular disease, type II diabetes, and chronic kidney disease [16][17][18][19]. The proposal to rename NAFLD to MAFLD of Eslam et al (2019) produced a consensus and subsequently changed the approach to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocardiography is a crucial emergency tool in a pre-hospital situation [1]. It is a useful non-invasive diagnostic technique for quickly identifying a variety of heart disorders, particularly acute coronary syndrome and electrico-cardiac arrhythmias [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a risk of arrhythmias or suspected ischemic heart disease are frequently advised to have their ECGs monitored [4][5]. It can be handled properly to aid in the diagnosis or management of a number of life-threatening illnesses [1]. In critical care settings, including the emergency room (ER), intensive care unit (ICU), and cardiac care unit (CCU), patients heavily depend on health providers for treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%